Are cytologic and histopathologic features of hot thyroid nodules different from cold thyroid nodules?. Issue 9 (12th June 2019) - Baser, Husniye; Topaloglu, Oya; Bilginer, Muhammet C.; Ulusoy, Serap; Kılıcarslan, Aydan; Ozdemir, Elif; Ersoy, Reyhan; Cakir, Bekir
Abstract: Background: We aimed to compare the cytology and histopathology results of hot, cold, and warm nodules in patients who had thyroidectomy due to toxic multinodular goiter (TMNG). Methods: Five hundred and nine thyroid nodules from 413 patients who had operation with TMNG were included in this retrospective study. The nodules were categorized as hot, cold, and warm groups. The cytology and histopathology results were compared. Results: The 509 thyroid nodules were grouped as hot (n = 364 [71.5%]), cold (n = 122 [24.0%]), and warm (n = 23 [4.5%]) according to scintigraphy. Cytological evaluations of 364 hot nodules were as follows: 80 (22%) nondiagnostic (ND), 259 (71.2%) benign, 17 (3.6%) atypia of undetermined significance/follicular lesion of undetermined significance (AUS/ FLUS), 2 (0.5%) follicular neoplasm/suspicious for follicular neoplasm (FN/SFN), 2 (0.5%) suspicious for malignancy (SM), and 4 (1.1%) malignant. The cytology of 122 cold nodules were ND in 25 (20.5%), benign in 86 (70.5%), AUS/FLUS in 8 (6.6%), FN/SFN in 1 (0.8%), and finally SM in 2 (1.6%). The 23 warm nodules were determined as ND, benign, and FN/SFN in 7 (30.4%), 15 (65.2%) and 1 (4.3%), respectively. There were no differences according to cytological results between groups ( P = .616). However, malignancy rate was 3.8% in hot nodules, it was found as 6.6% in cold nodules. The malignancy was detected in 4.3% of warm nodules. There were no differences in malignancy rates between groups ( P = .459). Conclusion: We demonstrated similar malignancy rates in hot nodules when compared with cold and warm nodules.